Kurban Hewan dalam Upacara Yadnya: Membunuh atau Memuliakan? - Asmarani, Ni Nyoman Oktaria (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
One of the worships performed by the Balinese Hindu community can be seen from the Yadnya ceremony. Yadnya itself means a sacrifice made sincerely to be offered to God, namely Ida Sang Hyang Widhi Wasa. In the process, Balinese Hindus used to use animals as sacrifices for the Yadnya ceremony. For animal welfare activists, the use of these animals is considered as something inappropriate because it means that animals are only meant to fulfill human needs. In fact, animals have the right to live, just like humans. Even so, there are actually many dimensions that can be seen from the use of animals in this Yadnya ceremony. This article will critically examine the culture of sacrificing animals in Yadnya and how animal welfare sees that culture. This objective will be elaborated through the answers to the questions: What is the rationale of Balinese Hindu community in using animals for Yadnya ceremony?; How are animals used in the Yadnya ceremony? and; How is animal sacrifice in various ceremonies seen by the perspective of animal welfare? The result of this bibliographical research shows that the use of animals as sacrifices in the Yadnya ceremony in Hinduism turned out to have a complex background. This treatment cannot simply be called killing animals because they contain values that are also believed to be able to respect the animal itself.